Novel CD3‐specific antibody induces immunosuppression via impaired phosphorylation of LAT and PLCγ1 following T‐cell stimulation. Issue 6 (10th April 2014) - Shiheido, Hirokazu; Aoyama, Takane; Takahashi, Honami; Hanaoka, Kaori; Abe, Tomoki; Nishida, Emi; Chen, Chen; Koga, Orie; Hikida, Masaki; Shibagaki, Yoshio; Morita, Akimichi; Nikawa, Takeshi; et al.
<x xml:space="preserve">Abstract</x> The activation of T cells is known to be accompanied by the temporary downmodulation of the TCR/CD3 complex on the cell surface. Here, we established a novel monoclonal antibody, Dow2, that temporarily induces downmodulation of the TCR/CD3 complex in mouse CD4+ T cells without activating T cells. Dow2 recognized the determinant on CD3ε; however, differences were observed in the binding mode between Dow2 and the agonistic anti‐CD3ε Ab, 145–2C11. An injection of Dow2 in vivo resulted in T‐cell anergy, and prolonged the survival of cardiac allografts without a marked increase in cytokine release. The phosphorylated forms of the signaling proteins PLC‐γ1 and LAT in Dow2‐induced anergic T cells were markedly decreased upon stimulation. However, the levels of phosphorylated LAT and PLCγ1 in Dow2‐induced anergic T cells could be rescued in the presence of the proteasome inhibitor MG‐132. These results suggest that proteasome‐mediated degradation is involved in hypophosphorylated LAT and PLCγ1 in Dow2‐induced anergic T cells. The novel CD3‐specific Ab, Dow2, may provide us with a unique tool for inducing immunosuppression.